Eksplorasi Bakteri Pendegradasi Hidrokarbon Pada Tanah Terkontaminasi Minyak Bumi - R.T. Manalu; A. Napoleon; A. Hermawan (SAINSTECH FARMA, 2016)
ABSTRACT This research aim to for the exploration of bacterium of decomposer hydrocarbon at land of contaminated petroleum which have potency of decomposing hydrocarbon in petroleum waste. Intake follow the example of the land for the research of this is conducted in some place which its land land of contaminated petroleum at area Benakat, Pengabuan And Rimau which is all area reside in the South Sumatra. A lot of and rich of mikroorganisme executed in Chemical Laboratory, Biology And Fertility of Land of Majors of Soil; of Faculty Agriculture of University Sriwijaya, Indralaya. Identify the bacterium conducted in Balai Besar Laboratorium Kesehatan (BBLK) and Analyse the TPH (Total Petroleum Hydrocarbon) executed in Chemical Laboratory Analyse The, Chemical Majors Faculty of Mathematics and Natural Sciences of University Sriwijaya. Time of Research Execution started by early August 2008 till December 2008. Research result indicate that there are 4 spesies of bacterium of origin of location Benakat, 2 spesies of bacterium of origin of Location Rimau and 6 spesies of bacterium of origin of Pengabaun location. Chosen bacterium capable to live on until hydrocarbon concentration 300 ppm is bacterium of type of Bacillus cereus, Pseudomonas aeruginosa, and Acinetobacter calcoaceticus. Chosen bacterium able to decomposing and elaborate the hydrocarbon by elaborating hydrocarbon compound become the source energi required for the activity of the bacterium so that reach the content TPH 1%.